Saotomia tuberculata, a new genus and species of Peritelini (Coleoptera; Curculionidae; Entiminae) from São Tomé, West Africa - Borovec, Roman; Anderson, Robert (Zootaxa, 2021)
Saotomia tuberculata, a new genus and species of Peritelini (Curculionidae; Entiminae) from São Tomé, West Africa is described. The new genus is most similar to the other African genera Dysommatus Marshal, 1933 and Fernandius Marshall, 1954. Important taxonomic characters are illustrated.